The Effects of the Perceived Behavioral Integrity of Managers on Employee Attitudes: A Meta-analysis - Davis, Anne L. (Journal of business ethics, 2006)
Perceived behavioral integrity involves the employee’s perception of the alignment of the manager’s words and deeds. This meta-analysis examined the relationship between perceived behavioral integrity of managers and the employee attitudes of job satisfaction, organizational commitment, satisfaction with the leader and affect toward the organization. Results indicate a strong positive relationship overall (average r = 0.48, p<0.01). With only 12 studies included, exploration of moderators was limited, but preliminary analysis suggested that the gender of the employees and the number of levels between the employee and the manager are potential moderators of the relationship. In the current sample of studies, country where the research was conducted did not seem to have any moderating effects. In addition to suggesting further investigation of potential moderators, we call for research that examines the relationship between behavioral integrity and outcomes that include individual behavior and organizational performance.